2021
DOI: 10.4209/aaqr.200547
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Expiratory Aerosols in a Room: Study Using a Bi-compartment and Bi-component Indoor Air Model

Abstract: Recent studies argue that inhalation of respiratory droplets in indoor environments is one of the significant routes of COVID-19 infection. In many cases, patients are isolated in hospitals and quarantine centers to minimize the spread. However, the rooms allocated to these patients are accessed by health care and sanitization workers a couple of times in a day. Since the expiratory activities release airborne droplets with certain viral load, there is a greater need to study the survival of these droplets in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Therefore, the use of mask and face shield should be used to prevent the virus [44][45][46]. The maintenance of ventilation in indoor situation is also very crucial to avoid the infection [48,49]. The maintenance of only a social distance of 2 meter as norm to avoid the virus is not corroborated by the present investigation because the aerosol created by the evaporation may remained suspended in the air for more than an hour.…”
Section: Summary and Discussionmentioning
confidence: 71%
“…Therefore, the use of mask and face shield should be used to prevent the virus [44][45][46]. The maintenance of ventilation in indoor situation is also very crucial to avoid the infection [48,49]. The maintenance of only a social distance of 2 meter as norm to avoid the virus is not corroborated by the present investigation because the aerosol created by the evaporation may remained suspended in the air for more than an hour.…”
Section: Summary and Discussionmentioning
confidence: 71%
“…In other words, large droplets settled faster than they evaporated, whereas small droplets evaporated faster than they settled (Bourouiba, 2020 ; Wells, 1934 ). Similarly, Bathula et al ( 2021 ) reported that the diameter of the dry droplet nuclei decreased to 32% of the original diameter of the wet droplet due to evaporation. In the present study, the droplets with the diameters 1 and 6 μm were capable of complete evaporation and remained in the air for about 5 min as the droplet nuclei with SARS-CoV-2 at midnight and midday, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…A N U S C R I P T 3 sneeze, and talking produced from the oral cavity (Johnson et al, 2011;Lee et al, 2019;Stadnytskyi et al, 2021;El Hassan et al, 2022), as well as aerosol dispersion inside a room (Inthavong et al, 2013;Heschl et al, 2014;Ji et al, 2018;Tao et al, 2020;Bathula et al, 2021;Crawford et al, 2021;Shah et al, 2021;Shrestha et al, 2021) and outdoor environments (Feng et al, 2020;Gorbunov, 2021). Additionally, studies (Zhu et al, 2006;Scharfman et al, 2016) demonstrated the oral cough produced a droplet-laden cough jet and puff dynamics, as well as review articles on the fluid dynamics of respiratory droplets (Dbouk and Drikakis, 2020;Mittal et al, 2020;Katre et al, 2021), and mitigation strategies for reducing viral transmission (Hui et al, 2012;Khosronejad et al, 2020;Salati et al, 2021).…”
Section: A C C E P T E D Mmentioning
confidence: 99%